Alexander Graham Bell family papers - Bell, Alexander Graham, 1847-1922.; Bell, Alexander Melville, 1819-1905.; Bell, Mabel Gardiner Hubbard, 1857-1923.; Fairchild, Marian, 1880-1962.; Hubbard, Gardiner G. (Gardiner Greene), 1822-1897.
Correspondence, diaries, journals, laboratory notebooks, patent records, speeches, writings, subject files, genealogical records, printed material, and other papers pertaining primarily to Bell's invention of the telephone (1876). Also includes material documenting his contributions to the education of the deaf and his interests in a wide range of scientific and technological fields including aviation, eugenics, and marine engineering. Includes bound volumes of the Beinn Bhreagh Recorder, a bulletin concerning Bell's laboratory and estate in Baddeck, N.S.; and volumes of the American Annals of the Deaf and Dumb, later American Annals of the Deaf. Correspondents include Edward Miner Gallaudet, Ulysses S. Grant, Joseph Henry, Helen Keller, George Kennan, S. P. Langley, Guglielmo Marconi, Simon Newcomb, John Wesley Powell, Theodore Roosevelt, William H. Taft, Charles Sumner Tainter, and Woodrow Wilson.
Family papers include papers of Bell's father, Alexander Melville Bell, relating chiefly to elocution and the physiology of speech; papers of Alexander Graham Bell's father-in-law, Gardiner Greene Hubbard; papers of Mabel Hubbard Bell including correspondence with her husband, Alexander Graham Bell; correspondence of their daughter, Marian Fairchild; and papers of other members of the Bell, Fairchild, Grosvenor, and Hubbard families.
Microfilm edition (edition filmed prior to arrangement of the Alexander Graham Bell Family Papers by the Library of Congress Manuscript Division) of selected scientific notebooks available
Negative microfilm edition of a poem, "The Tongue," (1861) by Alexander Bell (1792-1865) available through Library of Congress Photoduplication Service
Microfilm produced from originals now in the Manuscript Division.
Selected correspondence, scientific notebooks, journals, blueprints, articles, and photographs also available through the Library of Congress Web site.
Library of Congress Geography and Map Division.
Library of Congress Music Division.
Keywords: Bell, Alexander Graham, -- 1847-1922 -- Homes and haunts; Gallaudet, Edward Miner, -- 1837-1917 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Henry, Joseph, -- 1797-1878 -- Correspondence; Keller, Helen, -- 1880-1968 -- Correspondence; Kennan, George, -- 1845-1924 -- Correspondence; Langley, S. P. -- 1834-1906 -- Correspondence; Marconi, Guglielmo, -- marchese, -- 1874-1937 -- Correspondence; Newcomb, Simon, -- 1835-1909 -- Correspondence; Powell, John Wesley, -- 1834-1902 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Tainter, Charles Sumner, -- 1854-1940 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Bell family; Fairchild family; Grosvenor family; Hubbard family; American annals of the deaf; American annals of the deaf and dumb; Aeronautics; Deaf -- Education; Deaf -- Periodicals; Elocution; Eugenics; Marine engineering; Presidents -- United States; Science; Science -- Periodicals; Speech -- Physiological aspects; Technology; Telephone -- History; Baddeck (N.S.); Beinn Bhreagh recorder; Educators; Inventors